Case Report: CD19 CAR T-cell therapy following autologous stem cell transplantation: a successful treatment for R/R CD20-negative transformed follicular lymphoma with TP53 mutation - Zhang, Jinjing; Cai, Dali; Gao, Ran; Miao, Yuan; Cui, Yan; Liu, Zhenghua; Zhang, Heyang; Yan, Xiaojing; Su, Nan (Frontiers in Immunology, 2023)
Background: Follicular lymphoma (FL), a common indolent B-cell lymphoma, has the potential to transform into an aggressive lymphoma, such as diffuse large B-cell lymphoma (DLBCL). The outcome of patients with transformed follicular lymphoma (tFL) is poor, especially in patients with transformed lymphoma after chemotherapy and patients with progression within 24 months (POD24). Chimeric antigen receptor (CAR) T-cell therapy combined with autologous stem cell transplantation (ASCT) has promising antitumor efficacy.Case presentation: Here, we described a 39-year-old male patient who was initially diagnosed with FL that transformed into DLBCL with POD24, CD20 negativity, TP53 mutation, and a bulky mass after 3 lines of therapy, all of which were adverse prognostic factors. We applied a combination approach: CD19 CAR T-cell infusion following ASCT. Ibrutinib was administered continuously to enhance efficacy, DHAP was administered as a salvage chemotherapy, and ICE was administered as a bridging regimen. The patient underwent BEAM conditioning on days -7 -1, a total of 3.8 × 10 6 /kg CD34 + stem cells were infused on days 01 02, and a total of 10 8 CAR T cells (relmacabtagene autoleucel, relma-cel, JWCAR029) were infused on day 03. The patient experienced grade 2 cytokine release syndrome (CRS), manifesting as fever and hypotension according to institutional standards. There was no immune effector cellassociated neurotoxicity syndrome (ICANS) after CAR T-cell infusion. Finally, the patient achieved CMR at +1 month, which has been maintained without any other adverse effects.following ASCT for R/R tFL, thus providing new insight on therapeutic strategies for the future.